Motion planning, equivalence, infinite dimensional systems - Rouchon, Pierre (Zielona Góra: Uniwersytet Zielonogórski)
Motion planning, i.e., steering a system from one state to another, is a basic question in automatic control. For a certain class of systems described by ordinary differential equations and called flat systems (Fliess et al., 1995; 1999a), motion planning admits simple and explicit solutions.
Keywords: infinite dimensional control systems; motion planning; flatness, absolute equivalence; Pfaffian systems; delay systems; Gevrey functions